The Relation Between Economical And Environmental Factors And Malaria Incidence In Khartoum State-Sudan - Mahgoub, Afaf T. (Archives of Business Research, 2017)
Malaria incidence is intimately linked to environmental quality and economic status of the family. However, few studies have evaluated the associations between environmental factors and economic status of families and prevalence of malaria among their children. Prospective population-based study on malaria was carried in Khartoum State. Sample size was 400 families, distributed between three different socioeconomic strata. Different quantitative and qualitative methods of data collection were used (questionnaires, interviews and observations). The prevalence of malaria was performed for children under five years old. The study found that income was the strongest influencing factor (P=0.000) affecting negatively the prevalence of Malaria among children through affecting standard of living. Also there is strong relation between environmental factors (such as pit latrine and home size) and prevalence of malaria. Poverty and poor environment in home and around lead to increase malaria incidence.